MPACT OF CUSTOMER SATISFACTION TOWARDS PONDS SKIN CARE PRODUCT IN PERAMBALUR TOWN - Kavitha, Mrs.J.; Santhi, Prof.R. (IJRDO - Journal of Applied Management Science, 2017)
This study attempts to investigate the factors that influence the purchase intention of female customers towards skin care productsspecial referance with Perambalur town of Tamilnadu. A total of 60 current customers using cosmetics were approached to collect data, by means of questionnaires. They were analyzed utilizing the descriptive research technique.The research has been conducted to know the peoples expectation and satisfaction Towards Ponds Skin Care Product. The difficulties faced by the customers with regard to skin care products availability and quality were also inquired into and there by their overall satisfaction level was studied. This is a descriptive research and mainly primary data is used for the purpose of data collection through questionnaire. It was undertaken to determine the customer opinion and behavior of customers, price, quality, brand name are included in the study. Satisfaction level on ponds skin care products. Spss package program was used to analyze the data.